A clinical study to evaluate platelet count and serum albumin as independent prognostic factors in predicting the outcome in burn patients in a tertiary care hospital - Balachandran, Kavitha Jayanthi; Mohammed, Serbin (International Surgery Journal, 2020)
Background: Burns can affect the population of all age groups and regions. There has been a reduction in the mortality and morbidity of burn patients due to improvements in standards of medical care. Several laboratory values were proposed to indicate the prognosis of burns patients. Of these, the oldest is abbreviated burn severity index (ABSI), which includes variables such as sex, age, total burned body surface area (BSA), full-thickness injuries, and burns attributable to inhalation. Later the acute physiology and chronic health evaluation (APACHE) II and APACHE III scales which incorporates biochemical markers to improve predictive power evolved. Methods: In this study, in a tertiary care government institution, we attempt to assess platelet count and serum albumin independently in the prognosis of burns patient, in a background of sepsis. Results: For analysis, patients were divided into two groups- survivors and non-survivors as sepsis development and mortality was observed. There was a progressive decline in the platelet count in non-survivors, while the initial fall improved in those who survived. There was only a marginal difference between the two groups in serum albumin levels. Conclusions: A serial fall in platelet count is a predictor of sepsis and mortality in burn patients. It is an indicator of bone marrow depression and correlation with leucocyte count needs to be evaluated. In those patients where the initial fall in platelet count improved, survival rates were high. As a biochemical marker, serum albumin was not a reliable marker in predicting sepsis and mortality.